STUDENTS’ CRITICAL THINKING SKILLS DEVELOPMENT WITHIN PEDAGOGICAL SPECIALTIES OF MASTER'S EDUCATIONAL LEVEL IN THE CONTENT OF THE DISCIPLINE «PROFESSIONAL COMMUNICATION IN A FOREIGN LANGUAGE» - Kosharna, Natalia (Educological discourse, 2020)
The article is devoted to the issue of studying the ways of developing students’ critical thinking skills within pedagogical specialties of master’s educational level in the content of the discipline «Professional communication in a foreign language». It was found out that the development of future teachers’ critical thinking skills directly depends on developing their communicative skills in the field of professional activity. It is pointed out the need to apply an integrated approach (language and professional) in mastering a foreign language professional communication (the English language), which allows future teachers to communicate in professional, pedagogical, social and personal spheres of activity; to develop a critical style of thinking. Its characteristics are flexibility, reflexivity, awareness of the internal ambiguity of positions and points of view, alternative decisions, formation the following basic personality traits as sociability, creativity, mobility, independence, responsibility for the personal choice, decision and the results of the teachers’ activities.